Dominant Discourses and Teachers' Comparative Sensemaking through Internationally Sited Professional Development Experience - Emily W. Anderson (Gulf Education and Social Policy Review)
Abstract The United Arab Emirates' education policy agenda is focused on a singular goal: to be one of the top 20 countries in PISA 2022. The focus on PISA has become so robust in the UAE that it is now a central component of teachers' professional development. This article explores teachers' sensemaking of dominant education policy discourses through their experience in an internationally sited professional development program in Vietnam – a country whose 2015 PISA performance inspired the education policy reform in the UAE. The findings presented in this article highlight teachers' deficit framing of difference and their performative adoption of STREAM-focused practices to replicate Vietnam's 2015 PISA scores. This article concludes with recommendations for future research to better understand the ways in which dominant discourses inform teachers' professional development, and opportunities to expand teachers' roles in the policymaking process.